NiO added Zn1-xNixO (0 <= x <= 0.05) for thermoelectric power generation - Park, K.; Seong, J. K.; Kim, G. H. (ELSEVIER SCIENCE SA, 2009)
The Ni-added Zn1-xNixO (0.01 <= x <= 0.05) crystallized in ZnOss with a wurtzite structure, along with a small amount of NiOss with a cubic structure. The addition of NiO to ZnO showed a significant effect on the microstructure along with the development of the cubic NiO, yielding a smaller grain size. The sign of the Seebeck coefficient for all samples was negative over the entire temperature range (600-800 degrees C) i.e., n-type conduction. The addition of NiO to ZnO led to a dramatic increase in both the electrical conductivity and the absolute value of the Seebeck coefficient, providing a significantly improved thermoelectric power factor. Zn0.97Ni0.030 showed an outstanding power factor (1.76 x 10(-3) Wm(-1) K-2) at 800 degrees C due to a high conductivity (69.7 Omega(-1) cm(-1))and a large absolute value of the Seebeck coefficient (503 mu VK-1). The power factor was over 29 times higher than that of NiO-free ZnO (0.62 x 10(-4) Wm(-1) K-2). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: PARTIAL SUBSTITUTION; NACO2O4; ZNO; CO; MICROSTRUCTURE; CUALO2; CA